Production Volume Analysis Based on Maintenance Costs of Production Machines and Labor Productivity (Case Study On Convection Mukena Arrinda Collection Sukaraja Tasikmalaya Regency 2018-2021 Period) - Risma Anriyani (Journal of Indonesian Management, 2022)
The purpose of this study is to find out and analyze the influence of variable maintenance costs of production machinery and labor productivity on production volume in the Mukena Arrinda Collection Convection. The research method used is a case study. The data used is primary data and secondary data. Namely production machine maintenance cost data, labor productivity data, and production volume data for the period 2018-2021. Based on the results of research, it is known that the cost of maintenance (maintenance) of production machines and labor productivity simultaneously has a significant effect on production volume. The cost of maintenance (maintenance) of production machines partially affects the production volume. Labor productivity partially affects the volume of production. Therefore, the Mukena Arrinda Collection Convection must pay appropriate machine maintenance costs and pay attention to labor productivity so that the production volume increases.